Rural marketing : growing the non-urban consumer - Velayudhan, Sanal Kumar, 1955- (Routledge, 2024)
"Rural markets offer a sizable and resilient pool of consumers to organisations and marketers. This book offers a comprehensive understanding of the fundamentals of rural marketing that influence consumer behaviour within the framework of a rapidly changing economy. The book includes in-depth discussions on critical issues in rural markets as well as case-studies that examine their socio-cultural nuances, peculiarities, and their economic and technological environments; looks at concepts that are unique to rural markets from the perspective of the buyer and the marketer and analyses buying behaviour and its influences as well as the pricing, value, and positioning of products by brands; analyses emerging trends and the future of these markets and the introduction of digitization and ecommerce in rural areas; and offers marketing tools and a detailed understanding of rural markets for professionals working in small or low-income markets. The cutting-edge learning tools presented in this book will make it of interest to professionals, students and researchers working in rural marketing and management, business and economics, management studies, business planning, and marketing"-- Provided by publisher.
Keywords: Farm produce -- Marketing.; Produce trade.; elektronické knihy; electronic books